From the Canadian Library Association to the Canadian Federation of Library Associations: A Confluence of Evolution and Circumstance - DeYoung, Marie (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
This paper explores the history of the Canadian Library Association (CLA-ACB), from its inception in 1946 to its disbanding in 2016. While the CLA-ACB is not without accomplishments, especially in the areas of lobbying and advocacy, the association’s financial instability and challenges encountered in meeting member expectations ultimately led to its dissolution. Extensive consultation with the library community confirmed the continued need for a national library voice, best achieved through a new model, a federation of library associations.